Characteristics of Edible Film from Pigskin Gelatin - Sompie, M. (Faculty of Animal Science Universitas Gadjah Mada, 2014)
Edible film is thin layers that act as a barrier to the xternal factors and protect the food products. The addition of the plasticizer to the edible film is required to overcome film caused by extensive intermolecular forces. The potential development of pigskin of different ages as a raw material for manufacturing edible film have not been widely publicized. This research was aimed to determine the influence of animal age and concentration of plasticizer on the characteristic of edible film made form gelatin of pig skin. Study used a complete Randomized Design applying 2 factors (age and type of plasticizers), each consisted of 3 treatments (5, 7, and 9 mo of age and glycerol, sorbitol and polyethlyene glycol as the plasticizers). Results showed that the thickness of edible film was 0,133 to 0,226 mm, tensile strength was 2,820 to 5,637 MPa, elongation was 38,147-62-286% and water vapor transmission rate (WVTR) was 5,267 to 8,878 g.H2O.m-I. Interaction between the use of different animal age and concentrations of plasticizer was highly significant (P<0,01) water vapor transmission rate (WVTR) of edible film, but it had no significant effect (P>0,05) on the thickness, tensile strength and elongation of edible film. It was conclued that the pigskin gelatin from animal age of 7 months and glycerol as the plasticizer has the best edible film characteristics, and it can be applied as an edible coating.